A control-oriented semi-physical model for a direct expansion air conditioning system. (November 2014) - Xiangguo, Xu; Shiming, Deng; Xiaohong, Han; Xuejun, Zhang
It is always a challenge to develop appropriate mathematical model for a direct expansion (DX) air conditioning (A/C) system, whose operational parameters are highly coupled and behave non-linearly. Different modeling approaches have their own merits. However, none of the currently available modeling approaches can solely satisfy the requirement, in terms of accuracy and sensitivity, for simultaneous control of air temperature and humidity using a DX A/C system, without any inadequacies. On the other hand, when developing a model for the purpose of controller development rather than investigating complete system characteristics, the focus would be on several key components, and the modeling for other components that are relatively less important may be simplified. Therefore, it is possible to utilize different modeling approaches for different physical processes to develop a novel control-oriented hybrid model, named as semi-physical model (SPM). In this paper, rationales for using different modeling approaches for different physical processes of a DX A/C system are firstly discussed, followed by the development and validation of the SPM. The development of a SPM-based controller for the simultaneous control of air temperature and humidity is also briefly introduced, and its control perform acts as additional evidence for validating the SPM. Practical application: This paper presents a hybrid modeling method, which combines the complementary merits of various modeling approaches and avoid the inadequacies of them based on the analysis of the requirement of controller development. Such a new control-oriented hybrid modeling method can be applied to not only simultaneous temperature and humidity control using a variable-speed DX A/C system but also other control applications where control loops are coupled and system operational characteristics are complicated.